1996
DOI: 10.1111/1523-1747.ep12343819
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronic Acid and Dermatan Sulfate Are Selectively Stimulated by Retinoic Acid in Irradiated and Nonirradiated Hairless Mouse Skin

Abstract: All-trans retinoic acid (RA) has been shown to enhance subepidermal repair in photoaged hairless mice. The current study assesses the effects of RA on the glycosaminoglycan (GAG) content in irradiated and nonirradiated mouse skin. Mice were exposed to ultraviolet B (UVB) for 10 wk, after which they were treated either with 0.05% RA or with an ethanolpolyethylene glycol 400 vehicle three times a week for 10 or 20 wk. When assessed at the end of 10 wk of UVB irradiation, the GAG content had doubled, without a ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0
2

Year Published

1999
1999
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 32 publications
2
36
0
2
Order By: Relevance
“…Interestingly, several conditions that accelerate skin aging such as estrogen deficiency 13,14 are associated with loss of HA from the dermis, and treatments that counteract actinic skin aging such as retinoic acid increase dermal HA. 15,16 These results strongly suggest that dermal HA plays an important role during photoaging.…”
mentioning
confidence: 70%
See 2 more Smart Citations
“…Interestingly, several conditions that accelerate skin aging such as estrogen deficiency 13,14 are associated with loss of HA from the dermis, and treatments that counteract actinic skin aging such as retinoic acid increase dermal HA. 15,16 These results strongly suggest that dermal HA plays an important role during photoaging.…”
mentioning
confidence: 70%
“…Some studies reported increased HA content in UV-irradiated skin of mice, 39,40 whereas others reported reduced HA content. 16,41 The contradictory results of these studies might be attributable to the fact that different irradiation protocols were used that varied in dose and duration of the UV exposure and the time of analysis. It is likely that the acute effect of UV irradiation on dermal HA is different from the longterm effects of chronic UV irradiation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In photoShuko Terazawa and Hiroaki Nakajima have contributed equally to this work. aged skin, there is a marked deficiency of HA (Margelin et al 1996;Takahashi et al 1995Takahashi et al , 1996 in addition to the fragmentation and loss of type I collagen fibrils due to the up-regulated activity of matrix-metalloproteinase (MMP)-1 (Fisher et al 2008(Fisher et al , 2009). Available evidence indicates that naturally aged, sun-protected skin and photoaged skin share important molecular features, including connective tissue damage, elevated matrix metalloproteinase levels and reduced collagen production (Varani et al 2001(Varani et al , 2002.…”
Section: Introductionmentioning
confidence: 99%
“…Diferentes elementos da matriz são seletivamente estimulados ou modulados. O estímulo ao TGF-β, indiretamente, estimula a expressão gênica de vários componentes da matriz extracelular 49 .…”
Section: Maria Fernanda Demattê Soares Belicounclassified